Autism Prevalence Information And Diagnosis Processes In Cyprus, Greece And Malta - Petinou K; Vogindroukas I; Christopoulou M (Neuropsychiatric Disease and Treatment)
Kakia Petinou,1 Ioannis Vogindroukas,2 Maria Christopoulou3 1Department of Rehabilitation Sciences, Cyprus University of Technology, Limassol, 3036, Cyprus; 2Department of Education, University of Nicosia, Nicosia, 2417, Cyprus; 3Center of Neurodevelopmental Disorders, Nicosia, 1070, CyprusCorrespondence: Kakia Petinou, Email kakia.petinou@cut.ac.cyAbstract: The current paper follows the thematic review ‘Autism spectrum disorders without borders: prevalence and diagnosis across the globe’ aiming to highlight and familiarize readers with the challenges and heterogeneity related to the prevalence, and diagnostic processes of Autism Spectrum Disorders (ASD) from a cross-cultural and diverse geopolitical framework with a focus on Cyprus, Malta, and Greece. The study’s goal was twofold: (a) to document the prevalence and diagnostic processes in the aforementioned geographical areas and (b) to highlight similarities and differences in the prevalence and diagnostic process in ASD. The findings revealed similarities across all countries regarding the diagnostic tools implemented in ASD assessment tools and clinical observations. Some differences were observed in documenting prevalence rates due to methodological heterogeneity in the documentation procedures. Although preliminary, the current findings underscore the importance of research-driven investigations that can lead to larger-scale programs necessary for establishing policy-making and stakeholders’ involvement.Keywords: ASD, geographical regions, prevalence, diagnosis